A Microstrip Bandpass Filter Using Parallel Coupled Lines for 2.4 GHz WiFi Application - Deli Anggraini; Pakhrur Razi; Yulkifli; Khairi Budayawan (RESSTECH, 2025)
In this ever-evolving digital age, the need for wireless communication technology is becoming increasingly crucial in various sectors, such as commercial, industrial, educational, and even household. One of the most commonly used wireless technologies is WiFi (Wireless Fidelity), which enables high-speed wireless internet connections and supports user mobility efficiently. To ensure optimal WiFi performance, a frequency filter capable of selectively operating at specific frequencies, such as the 2.4 GHz band, is required. This study aims to characterize a bandpass filter for 2.4 GHz WiFi applications. The bandpass filter design employs a parallel coupled lines structure. Simulation results show that the filter has a center frequency of 2.45 GHz with a return loss of −28.6 dB, insertion loss of −1.61 dB, and a bandwidth of 93 MHz, which aligns with the specifications. However, measurement results after fabrication showed differences, namely a center frequency of 2.47 GHz, return loss of −25.65 dB, insertion loss of −3.55 dB, and bandwidth of 93 MHz. In conclusion, although the simulation performance meets the specifications, the fabricated performance shows deviations that are likely caused by fabrication tolerances and imperfections in the fabrication process.